STRATEGI GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA PENDIDIKAN INKLUSI DALAM KURIKULUM REGULAR DENGAN MODIFIKASI (STUDI PADA SEKOLAH MENENGAH AL FIRDAUS SUKOHARJO TAHUN AJARAN 2015/2016) - Pujihastuti, Nanik; Rejekiningsih, Triana (PKn Progresif, 2016)
The purpose of this study are : (1) to describe the strategies of Pancasila and Civic Education  teachers on the Inclusive Education in the Regular Education Curriculum with modifications; (2) to explain the effects of Pancasila and Civic Education Teachers? strategies toward the regular students and the slow learners; (3) to find the enabling and inhibiting factors of the Pancasila and Civic Education Teachers? strategies on the Inclusive Education in the Regular Education Curriculum with modifications. This study is the descriptive qualitative research. The research data was obtained from the informants, places, and the documents. Purposive sampling was used for the sampling technique. Interviews, observations, and the documents analysis were used to collect the data. The data validity used the data and method triangulations. To analyze the data, an interactive analysis model was used. Based on the research findings, it can be concluded : (1) Pancasila and Civic Education  teachers? strategies on the Inclusive Education in the Regular Education Curriculum with modifications as follow : a) making the teaching planning for regular and special needed (autism) students; b) applying the scientific, lecturing, question and answer, presentation, and problem based learning approaches, and applying the knowledge, attitudes, and skills; c) guiding students; d) creating the conducive and fun learning situation; e) having a good coordination with the special a particular advised teacher; 2) the impacts of Pancasila and Civic Education teachers? strategies toward students as follow : a) civics knowledge, regular students were able to understand well, but the slow learners were not. It was because of the slow learner capability is only capable of up to 5 th grade; b) civics characteristics, regular students were able to showing the private characteristics, such as responsibility, discipline, and showing the public characteristics such as listening friends? opinion, are not showing the discrimination. On the other hand, slow learners tended to showing the private characteristics that was responsibility; c) civics skills, regular students and slow learners were able to give opinion; 3) the enabling and inhibiting factors of Pancasila and Civic Education teachers? strategies on the Inclusive Education in the Regular Education Curriculum with modifications as follow : a) the enabling factors are (1) there was the particular advised teacher; (2) the adequate facilities and infrastructures such as a Puspa room, school?s WIFI, and library; (3) students? attitude that supported the implementation of teachers? strategies in inclusive education; b) the inhibiting factors are (1) there are no variation in teachers? strategies; (2) the allocation of a relatively short time; (3) there are still no special guides for regular curriculum with modifications.